Radiofrequency or cryoablation or medical therapy for paroxysmal atrial fibrillation: An indirect comparison of effectiveness - Roberto Brunoro; Lorenzo Di Spazio; Melania Rivano; Luca Cancanelli; Chiara Nunzia Fasano Celentano; Daniele Mengato; Andrea Messori (Journal of Arrhythmia)
Abstract Background Paroxysmal atrial fibrillation (PAF) is commonly treated with pharmacological therapies, but these may be insufficient for symptom control. Radiofrequency and cryoballoon ablation have emerged as alternative strategies. This study aimed to compare the efficacy of cryoballoon ablation, radiofrequency ablation, and anti‐arrhythmic drugs as initial therapies for symptomatic PAF based on randomized trial data. Methods Data were extracted from randomized trials, and individual patient data were reconstructed from Kaplan–Meier curves using artificial intelligence techniques. Time‐to‐event analysis was performed to evaluate arrhythmia recurrence, with hazard ratios (HRs) as the primary measure of efficacy. A heterogeneity analysis was conducted to assess variability between studies. Results Five randomized trials were included in the analysis. Significant between‐trial heterogeneity was observed. Both cryoballoon ablation (HR 0.48; 95% CI: 0.36–0.63; p < .001) and radiofrequency ablation (HR 0.54; 95% CI: 0.37–0.80; p = .002) demonstrated superior efficacy compared to anti‐arrhythmic drug therapy in reducing arrhythmia recurrence. Conclusions Cryoballoon and radiofrequency ablation are more effective than anti‐arrhythmic drugs for initial therapy in symptomatic PAF. These findings support the use of ablation techniques as preferred interventions in this patient population.